The Impact of Combination Therapy on Infliximab Levels and Antibodies in Children and Young Adults With Inflammatory Bowel Disease. Issue 6 (26th April 2018) - Chi, Lisa Yue; Zitomersky, Naamah Levy; Liu, Enju; Tollefson, Sophia; Bender-Stern, Julia; Naik, Snehal; Snapper, Scott; Bousvaros, Athos
Abstract: Goal: The aim of this study was to evaluate the effect of combination therapy with methotrexate or 6-mercaptopurine on infliximab levels (IFXL) and antibodies to infliximab (ATI). Background: Infliximab (IFX) is a highly effective therapy for inflammatory bowel disease (IBD). Unfortunately, 25%–50% of patients will lose response to IFX. Loss of response is correlated with low IFXL and ATI formation which accelerates drug clearance. Combination therapy is thought to decrease ATI formation. Methods: We performed a cross-sectional analysis of 223 pediatric and young adult patients with IBD on IFX. IFXL and ATI were measured and compared between subjects on current combination therapy, prior combination therapy, and IFX monotherapy. Results: Eighty-four (37.7%) patients were on combination therapy and 139 (62.3%) were on IFX monotherapy. Within the current monotherapy group, 112 (80.6%) had previously been on combination therapy, while 27 (19.4%) had never been on a concomitant immunomodulator. Patients currently on combination therapy had a higher IFXL (17.00 ± 1.33 μg/mL) than those currently on IFX monotherapy (13.18 ± 1.26 μg/mL), P < 0.01. IFXL was lowest in patients who had never been on combination therapy (11.53 ± 2.05 μg/mL) and highest in patients currently on combination therapy (17.00 ± 1.33 μg/mL). Patients currently on combination therapy had a lower rate of detectable ATI (9.5%) compared with those on monotherapy (20.0%) in multivariate analysis (odds ratio [OR]: 0.3; 95% confidence interval (CI), 0.1–0.7, P < 0.01). Conclusions: Current or prior combination therapy is associated with higher IFXL and lower rates of ATI formation.